Privacy and Security in Digital Health Contact-Tracing: A Narrative Review - Shehani Pigera; Paul van Schaik; Karen Renaud; Miglena Campbell; Petra Manley; Pierre Esser (Applied Sciences)
(1) Background: Contact-tracing apps only achieve their aims if the majority of the population installs and actively engages with them. Such acceptance depends on public perceptions and are likely influenced by privacy and security concerns. Therefore, this review evaluates public perceptions towards the privacy and security of contact-tracing apps used during the recent COVID-19 pandemic, with a focus on identifying factors that influence acceptance. (2) Methods: A systematic literature review was performed. A total of 114 articles were retained as per the inclusion criteria, which included quantitative, qualitative, and mixed-methods studies. The data were analysed using thematic analysis. (3) Results: Eight main themes were derived: privacy, data protection and control, trust, technical issues, perceived benefit, knowledge and awareness, social influence, and psychological factors. (4) Conclusions: Improving privacy standards and the awareness of the digital contact-tracing process will encourage the acceptance of contact-tracing apps.